Механізм лінійних переміщень - Павленко, І. І.; Валявський, І. А.; Валявський, А. І.; Pavlenko, I.; Valiavskyi, I.; Valiavskyi, A.; Павленко, И. И.; Валявский, И. А.; Валявский, А. И. (Український інститут промислової власності, 2009)
Корисна модель відноситься до галузі верстатобудування, а саме до технологічного обладнання з паралельною кінематикою. A mechanism of linear displacements has a drive, toothed and screw gears, long hollow beam and tubular body. The screw gear is placed in hollow beam with nut capable of linear displacing with respect to the tubular body.
Mechanism of linear displacements